Graphite negative electrode active material and preparation method thereof, negative electrode plate, secondary battery and electric device

By using graphite negative electrode active material in secondary batteries, the percentage content of crystalline carbon mass in the interior and surface areas is between 10% and 35%, the problem of insufficient cycle life of secondary batteries is solved, and higher cycle stability and energy density are achieved.

CN119852340AActive Publication Date: 2025-04-18CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202311679097.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-07
Publication Date
2025-04-18
Estimated Expiration
2043-12-07

Smart Images

  • Figure CN119852340A_ABST
    Figure CN119852340A_ABST
Patent Text Reader

Abstract

The invention provides a graphite negative electrode active material and a preparation method thereof, and a negative electrode plate, a secondary battery and an electric device containing the graphite negative electrode active material. A particle body of the graphite negative electrode active material comprises an internal region and a surface layer region at least partially surrounding the internal region, the surface layer region is a region formed by extending the surface of the particle body of the graphite negative electrode active material to the interior of the particle by a distance of 30nm, and the mass percentage content of crystalline carbon in the internal region is marked as eta 1, the mass percentage content of the crystalline carbon in the surface layer region is recorded as eta 2, and 10% < = eta 1-eta 2 < = 35%. The graphite negative electrode active material can improve the cycle performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of battery technology, and specifically relates to a graphite negative electrode active material and a preparation method thereof, a negative electrode sheet, a secondary battery and an electrical device. Background Art

[0002] In recent years, secondary batteries have been widely used in energy storage power systems such as hydropower, thermal, wind and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields.

[0003] As the requirements for the endurance of electrical devices continue to increase, more stringent requirements are placed on the cycle life of secondary batteries. How to further improve the cycle life of secondary batteries is a technical problem that those skilled in the art need to solve urgently. Summary of the invention

[0004] The purpose of the present application is to provide a graphite negative electrode active material and a preparation method thereof, a negative electrode plate, a secondary battery and an electric device. The graphite negative electrode active material improves the battery cycle performance while maintaining a good capacity.

[0005] In a first aspect, the present application provides a graphite negative electrode active material, wherein a particle body of the graphite negative electrode active material comprises an internal region and a surface region at least partially surrounding the internal region, wherein the surface region refers to a region extending 30 nm from the surface of the particle body of the graphite negative electrode active material to the interior of the particle, the mass percentage of crystalline carbon in the internal region is denoted as η1, the mass percentage of crystalline carbon in the surface region is denoted as η2, and 10%≤η1-η2≤35%.

[0006] The relatively lower crystalline carbon mass percentage in the surface area of ​​the graphite negative electrode active material compared to the internal area means that the carbon atoms in the surface of the graphite negative electrode active material are arranged in a relatively irregular manner, making the interaction force between its molecules more complex, resulting in higher strength and hardness than the internal area of ​​the graphite negative electrode active material. On the one hand, the graphite negative electrode active material retains a higher degree of particle integrity during the cold pressing process, reducing the occurrence of side reactions, which is beneficial to the improvement of battery cycle stability. At the same time, during the cycle process, active ions are easily embedded and de-embedded in the surface area of ​​the graphite negative electrode active material with low crystallinity, which can reduce the expansion rate of the secondary battery during a long cycle and further improve the cycle stability of the battery. The relatively high crystallinity in the internal area of ​​the graphite negative electrode active material allows the material to reduce cycle expansion and improve cycle performance while taking into account high capacity and high pressure density, so that the energy density of the battery will not be greatly attenuated.

[0007] In any embodiment, 75%≤η1≤99%, optionally 80%≤η1≤95%.

[0008] The crystalline carbon mass percentage in the inner region of the particle body of the graphite negative electrode active material is within the above range, which is conducive to maintaining the high capacity of the graphite negative electrode active material; and the graphite negative electrode active material will not cause lattice interlacing due to excessive internal defects, so that the graphite negative electrode active material always maintains excellent electrochemical performance during long-term cycling, reducing the probability of battery performance "diving".

[0009] In any embodiment, 55%≤η2≤75%, optionally 60%≤η2≤70%.

[0010] The crystalline carbon mass percentage in the surface area of ​​the graphite negative electrode active material particle body within the above range is beneficial to reducing the physical rebound of the graphite negative electrode active material after cold pressing, reducing the expansion rate of the electrode during the cycle, thereby improving the cycle stability of the secondary battery.

[0011] In any embodiment, the graphite negative electrode active material has a graphitization degree of 88%-95%, and optionally 90%-95%.

[0012] It can be understood that the degree of graphitization is an overall measure of the crystallinity of the graphite negative electrode active material. By regulating the different mass contents of crystalline carbon in the internal region and the surface region of the graphite negative electrode active material, the graphite negative electrode active material can have a suitable degree of graphitization, taking into account the capacity and cycle stability of the graphite negative electrode active material.

[0013] In any embodiment, the volume distribution particle size Dv50 of the graphite negative electrode active material is 7.5 μm-14.5 μm, and optionally 8.5 μm-12.5 μm.

[0014] The graphite negative electrode active material with a volume distribution particle size Dv50 within the above range can provide a certain ion channel without causing excessive side reactions due to too small a particle size and too large a specific surface area, and can take into account both kinetic performance and cycle stability.

[0015] In any embodiment, the specific surface area of ​​the graphite negative electrode active material is 1.25 m 2 / g-1.95m 2 / g, optional 1.35m 2 / g-1.75m 2 / g.

[0016] The graphite negative electrode active material has a low specific surface area, so that the graphite negative electrode active material can not only take advantage of the relatively low mass content of crystalline carbon in the surface area to reduce battery expansion, but also reduce the probability of side reactions through the relatively low specific surface area to improve the cycle stability of the battery.

[0017] In any embodiment, the particle size distribution of the graphite negative electrode active material (Dv90-Dv10) / Dv50 is 1.0-1.6, and can be optionally 1.1-1.5.

[0018] Controlling the particle size distribution of the graphite negative electrode active material within the above range is conducive to improving the compaction of the graphite negative electrode active material and improving the compaction density of the negative electrode film layer. In other words, the cold pressing pressure required for the negative electrode plate to achieve the same compaction density is smaller, thereby reducing the probability of cracking of the graphite negative electrode active material during the cold pressing process, and further improving the integrity of the graphite negative electrode active material during the processing process; and the small stress inside the graphite negative electrode active material particles is conducive to maintaining the long-period pore structure of the plate during the cycle process, and the original pore structure of the plate can be maintained during the cycle process, so that the lithium ion lithium insertion path remains unobstructed, while reducing the re-filming of the graphite negative electrode active material during the charging process, and improving the kinetic performance, cycle life and storage stability. Furthermore, the particle size distribution within the above range can also improve the uniformity of lithium insertion between the graphite negative electrode active material particles, reduce polarization, avoid lithium precipitation caused by uneven current density, and help achieve long-term cycle stability. In addition, the particle size distribution within the above range can also help improve the processing performance of the electrode, and will not affect the uniformity of slurry stirring due to excessive small particles in the graphite negative electrode active material, which is beneficial to improving the uniformity and stability of the electrode quality and helping to achieve long-cycle stability.

[0019] In any embodiment, the powder compaction density of the graphite negative electrode active material under a pressure of 49000N is 1.75g / cm 3 -1.88g / cm 3 , optional 1.78g / cm 3 -1.84g / cm 3 .

[0020] Graphite negative electrode active materials with a powder compaction density within the above range are easy to maintain high particle integrity during the cold pressing process, which helps to improve the cycle life of the secondary battery.

[0021] In any embodiment, the tap density of the graphite negative electrode active material is 1.05 g / cm 3 -1.30g / cm 3 .

[0022] In any embodiment, the gram capacity of the graphite negative electrode active material is 345 mAh / g-355 mAh / g, and can be optionally 347 mAh / g-353 mAh / g.

[0023] The graphite negative electrode active materials with gram capacity within the above range will not undergo significant lattice expansion during the charge and discharge process due to the high graphitization of the graphite negative electrode active materials; nor will they be difficult to compact due to the low graphitization of the graphite negative electrode active materials. In order to achieve the same electrode compaction density, a higher cold pressing pressure is required, which will cause cracks during the cold pressing process and generate new interfaces during the cycle process to consume too much active lithium, thereby comprehensively improving the cycle life of the secondary battery.

[0024] In any embodiment, the graphite negative electrode active material I D / I G is 0.05-0.10, among which I D / I G is the ratio of the D peak intensity to the G peak intensity obtained from the Raman spectrum, I D Indicates that the Raman spectrum is at 1350±100cm -1 The D peak intensity at I G Indicates that the Raman spectrum is at 1580±100cm -1 The G peak intensity at .

[0025] I of graphite negative electrode active materials D / I G It can be used to characterize the surface disorder of graphite negative electrode active materials. Different from the graphite negative electrode active materials that are post-coated on the surface of the graphite particle body, the graphite negative electrode active materials provided in the embodiments of the present application have amorphous carbon on the surface and have a lower surface disorder. The amorphous carbon in the active material that is post-coated with amorphous carbon on the surface of the graphite particle body is usually derived from the coated organic resin, which generates amorphous carbon under low-temperature carbonization, so that the amorphous carbon in the coating layer has a high surface disorder; while the surface area and the internal area of ​​the graphite negative electrode active material provided in the embodiments of the present application are derived from the same precursor and undergo the same heat treatment process, so the amorphous carbon of the graphite negative electrode active material is evenly distributed in the surface area of ​​the graphite negative electrode active material, so that the surface area of ​​the graphite negative electrode active material has a low crystalline carbon content and a low surface disorder. This allows the graphite negative electrode active material to take advantage of amorphous carbon, improve the battery's kinetic performance and reduce the cycle expansion rate of the electrode, while preventing excessive side reactions and a significant drop in battery capacity due to the high degree of disorder on the surface of the graphite negative electrode active material, thereby comprehensively improving the battery's cycle stability.

[0026] In any embodiment, the interlayer spacing of the surface area of ​​the graphite negative electrode active material is recorded as d1, the interlayer spacing of the internal area of ​​the graphite negative electrode active material is recorded as d2, and the graphite negative electrode active material satisfies d1>d2; optionally, 0.3365nm≤d1≤0.3378nm; optionally, 0.3358nm≤d2≤0.3364nm.

[0027] In any embodiment, the graphite negative electrode active material includes both primary particles and secondary particles; optionally, based on the total number of primary particles and secondary particles in the graphite negative electrode active material, the number of the secondary particles accounts for less than or equal to 50%.

[0028] Graphite negative electrode active materials with a low proportion of secondary particles are conducive to maintaining the particle integrity of graphite negative electrode active materials during battery preparation, reducing the generation of new interfaces, reducing the consumption of active lithium during the cycle, and further improving the cycle stability of secondary batteries. At the same time, a certain number of secondary particles can reduce the expansion of the negative electrode while taking into account the kinetic performance of the secondary battery, so that the battery cell has a kinetic window for the entire life cycle, and will not cause lithium precipitation due to uneven current distribution, causing the battery capacity to decay sharply and the battery life to deteriorate sharply, thereby comprehensively improving the cycle stability of the battery.

[0029] The second aspect of the present application provides a method for preparing a graphite negative electrode active material, comprising the following steps: providing raw materials; processing the raw materials to obtain an intermediate product; graphitizing the intermediate product to obtain a graphitized product; screening the graphitized product to obtain a graphite negative electrode active material; the particle body of the graphite negative electrode active material includes an internal region and a surface region that at least partially surrounds the internal region, the surface region refers to a region extending 30 nm from the surface of the particle body of the graphite negative electrode active material to the interior of the particle, the mass percentage of crystalline carbon in the internal region is denoted as η1, the mass percentage of crystalline carbon in the surface region is denoted as η2, and 10%≤η1-η2≤35%.

[0030] In any embodiment, the maximum power of the graphitization process is 70%-90% of the rated power of the graphitization process equipment.

[0031] In any embodiment, the temperature of the graphitization treatment is 2600°C to 3000°C.

[0032] In any embodiment, the graphitization treatment time is 10 hours to 50 hours.

[0033] In any embodiment, the raw material includes one or more of petroleum coke, needle coke, and asphalt coke, and needle coke can be selected.

[0034] In any embodiment, based on the total volume of the raw material, the volume proportion of the fiber-type structure in the raw material is greater than or equal to 55%, and can be optionally 58%-70%.

[0035] Raw materials with more fiber-type structures are conducive to improving the compaction density and gram capacity of graphite negative electrode active materials, so that the graphite negative electrode active materials retain a high degree of integrity during the compaction process, and the battery has a high cycle life and good energy density; but too high a proportion of fiber-type structures will increase the cost and expansion rate of graphite negative electrode active materials and deteriorate kinetic performance. Raw materials with a volume proportion of fiber-type structures within the above range have both low costs and good gram capacity of graphite, and the battery cell has a full life cycle kinetic window, thereby comprehensively improving the long-term cycle life and electrochemical performance of the battery.

[0036] In any embodiment, the processing of raw materials specifically includes the following steps: crushing, shaping and grading the raw materials to obtain a first precursor; granulating the first precursor to obtain a second precursor; and low-temperature carbonizing the first precursor and the second precursor to obtain the intermediate product.

[0037] A third aspect of the present application provides a negative electrode sheet, comprising a graphite negative electrode active material in any embodiment or a graphite negative electrode active material prepared by a preparation method in any embodiment.

[0038] In any embodiment, the compaction density of the negative electrode film layer is 1.5 g / cm 3 ~1.65g / cm 3 .

[0039] The fourth aspect of the present application provides a secondary battery, comprising the negative electrode plate of the third aspect of the present application.

[0040] A fifth aspect of the present application provides an electrical device, comprising the secondary battery of the fourth aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.

[0042] Figure 1 is a schematic diagram of a cross-sectional image of a particle of a graphite negative electrode active material of the present application;

[0043] Figure 2 is a schematic diagram of an embodiment of a secondary battery of the present application;

[0044] Figure 3 is an exploded schematic diagram of an embodiment of a secondary battery of the present application;

[0045] Figure 4 is a schematic diagram of an embodiment of a battery module of the present application;

[0046] Figure 5 is a schematic diagram of an embodiment of a battery pack of the present application;

[0047] Figure 6 yes Figure 5 An exploded schematic diagram of an embodiment of a battery pack is shown;

[0048] Figure 7 It is a schematic diagram of one embodiment of an electric device including the secondary battery of the present application as a power source.

[0049] In the drawings, the drawings may not be drawn according to the actual scale. The reference numerals are as follows: 1 battery pack, 2 upper box, 3 lower box, 4 battery module, 5 secondary battery, 51 housing, 52 electrode assembly, 53 cover plate, 100 graphite negative electrode active material, 101 surface area, 102 internal area. DETAILED DESCRIPTION

[0050] Below, the graphite negative electrode active material and its preparation method, negative electrode sheet, secondary battery and electric device containing the same are described in detail with appropriate reference to the drawings, and the embodiments of the present application are specifically disclosed. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0051] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0052] If not otherwise specified, all embodiments and optional embodiments of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.

[0053] Unless otherwise specified, all technical features and optional technical features of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.

[0054] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0055] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0056] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0057] If not specifically stated, the terms used in this application have the commonly known meanings generally understood by those skilled in the art.

[0058] If not otherwise specified, the values ​​of the parameters mentioned in this application can be measured using various test methods commonly used in the art, for example, they can be measured according to the test methods given in this application.

[0059] If not otherwise specified, in the present application, the term "active ions" refers to ions that can be intercalated and extracted back and forth between the positive electrode and the negative electrode of a secondary battery, including but not limited to lithium ions.

[0060] In the present application, the terms "plurality" and "multiple" refer to two or more.

[0061] The electrochemical performance of carbon materials is often related to the mass content of their crystalline carbon. Carbon materials with high crystalline carbon mass content usually have higher capacity, but the crystalline carbon layer spacing is low. During long cycles, the repeated embedding and de-embedding of active ions will cause the lattice to expand greatly, resulting in a high cycle expansion rate of the electrode and poor cycle stability.

[0062] Based on this, the present application provides a graphite negative electrode active material, wherein the particle body of the graphite negative electrode active material includes an internal region and a surface region that at least partially surrounds the internal region, wherein the surface region refers to a region extending 30 nm from the surface of the particle body of the graphite negative electrode active material to the interior of the particle, the mass percentage of crystalline carbon in the internal region is denoted as η1, the mass percentage of crystalline carbon in the surface region is denoted as η2, and 10%≤η1-η2≤35%.

[0063] Figure 1 Schematic diagram of a cross-sectional image of a particle of the graphite negative electrode active material 100 of the present application. Figure 1 As shown, the region extending 30 nm inward from the particle body surface of the graphite negative electrode active material 100 is the surface region 101 , and the region inside the surface region 101 is the internal region 102 .

[0064] In the present application, the mass percentage of crystalline carbon can be tested by methods known in the art. As an example, a slice with a thickness of about 20nm to 50nm is cut from the middle of the graphite negative electrode active material particle body by a focused ion beam (FIB), and then the slice is tested by transmission electron microscopy (TEM). The content of different bond carbon elements in graphite is tested by transmission electron microscopy-energy loss spectroscopy (TEM-EELS) using energy loss spectroscopy (EELS), and the sp 2 Carbon is taken as crystalline carbon, and the mass percentage of crystalline carbon in different regions of the graphite negative electrode active material is determined by integrating the area ratio. At least 10 points and at least 5 samples are selected in each region, and the average mass percentage of crystalline carbon in different regions is calculated.

[0065] In some embodiments, η1-η2 is 10%, 13%, 15%, 16%, 20%, 22%, 24%, 25%, 26%, 28%, 30%, 31%, 35% or any range therebetween. For example, η1-η2 can be 10%-31%, 10%-28%, 13%-35%, 13%-31%, 13%-28%, 15%-35%, 15%-31%, 15%-28%, 16%-35%, 16%-31%, 16%-28%, 20%-35%, 20%-31%, 20%-28%, 22%-35%, 22%-31%, 24%-35%, 24%-31%, 25%-35%, 25%-31%.

[0066] The relatively lower crystalline carbon mass percentage in the surface area of ​​the graphite negative electrode active material compared to the internal area means that the carbon atoms in the surface of the graphite negative electrode active material are arranged in a relatively irregular manner, making the interaction between its molecules more complex, resulting in higher strength and hardness than the internal area of ​​the graphite negative electrode active material. On the one hand, the graphite negative electrode active material retains a higher degree of particle integrity during the cold pressing process, reducing the occurrence of side reactions, which is beneficial to the improvement of battery cycle stability. At the same time, during the cycle process, active ions are easily embedded and de-embedded in the surface area of ​​the graphite negative electrode active material with low crystallinity, which can reduce the expansion rate of the secondary battery during a long cycle and further improve the cycle stability of the battery. The relatively high crystallinity in the internal area of ​​the graphite negative electrode active material allows the material to reduce cycle expansion and improve cycle performance while taking into account the high pressure density of the battery and achieving high capacity of the battery.

[0067] In some embodiments, 75%≤η1<99%, optionally 80%≤η1≤95%.

[0068] In some embodiments, η1 is 75%, 80%, 85%, 90%, 95%, 99%, or any range therebetween.

[0069] The crystalline carbon mass percentage in the inner region of the particle body of the graphite negative electrode active material is within the above range, which is conducive to maintaining the high capacity of the graphite negative electrode active material; and the graphite negative electrode active material will not cause lattice interlacing due to excessive internal defects, so that the graphite negative electrode active material always maintains excellent electrochemical performance during long-term cycling, reducing the probability of battery performance "diving".

[0070] In some embodiments, 55%≤η2≤75%, optionally 60%≤η2≤70%.

[0071] In some embodiments, η2 is 55%, 57%, 60%, 63%, 65%, 67%, 70%, 73%, 75%, or any range therebetween.

[0072] The crystalline carbon mass percentage in the surface area of ​​the graphite negative electrode active material particle body within the above range is beneficial to reducing the physical rebound of the graphite negative electrode active material after cold pressing, reducing the expansion rate of the electrode during the cycle, thereby improving the cycle stability of the secondary battery.

[0073] In some embodiments, the graphite negative electrode active material has a graphitization degree of 88%-95%, and optionally 90%-95%.

[0074] As used herein, the term "degree of graphitization" refers to an index measuring the degree to which carbon atoms form a close-packed hexagonal graphite crystal structure.

[0075] In the present application, the degree of graphitization of the graphite negative electrode active material can be tested by methods known in the art. As an example, high-purity silicon powder (purity ≥ 99.99%) is used as an internal standard for calibration, and the graphite negative electrode active material: silicon is mixed in a weight ratio of 5:1, ground evenly, and pressed into a sheet for sample preparation. An X-ray diffractometer (such as Bruker D8 Discover) is used for testing, and JIS K 0131-1996 and JB / T 4220-2011 are referred to to obtain the average interlayer spacing d002 of the (002) crystal plane in the crystal structure of the graphite negative electrode active material, and then the degree of graphitization is calculated according to the formula g = (0.344-d002) / (0.344-0.3354) × 100%. In the above formula, d002 is the average interlayer spacing of the (002) crystal plane in the crystal structure of the graphite negative electrode active material expressed in nanometers (nm).

[0076] In some embodiments, the graphite negative electrode active material has a degree of graphitization of 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95% or any range therebetween.

[0077] It can be understood that the degree of graphitization is an overall measure of the crystallinity of the graphite negative electrode active material. By regulating the different mass contents of crystalline carbon in the internal region and the surface region of the graphite negative electrode active material, the graphite negative electrode active material can have a suitable degree of graphitization, taking into account the capacity and cycle stability of the graphite negative electrode active material.

[0078] In some embodiments, the volume distribution particle size Dv50 of the graphite negative electrode active material is 7.5 μm-14.5 μm, and optionally 8.5 μm-12.5 μm.

[0079] As used herein, the term "volume distribution particle size Dv50" refers to the particle size corresponding to when the cumulative volume distribution number of particles reaches 50% in the particle size distribution curve.

[0080] In the present application, the volume distribution particle size Dv50 of the active material can be tested by methods known in the art. As an example, referring to GB / T 19077-2016, it is measured by a laser particle size analyzer. The testing instrument can be a Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.

[0081] In some embodiments, the volume distribution particle size Dv50 of the graphite negative electrode active material is 7.5 μm, 8.5 μm, 9.5 μm, 10.5 μm, 11.5 μm, 12.5 μm, 13.5 μm, 14.5 μm, or any range therebetween.

[0082] The graphite negative electrode active material with a volume distribution particle size Dv50 within the above range can provide a certain ion channel without causing excessive side reactions due to too small a particle size and too large a specific surface area, and can take into account both kinetic performance and cycle stability.

[0083] In some embodiments, the specific surface area of ​​the graphite negative electrode active material is 1.25 m 2 / g-1.95m 2 / g, optional 1.35m 2 / g-1.75m 2 / g.

[0084] In the present application, the specific surface area of ​​the graphite negative electrode active material can be tested by methods known in the art. As an example, referring to GB / T 19587-2017, the specific surface area analysis test method of nitrogen adsorption is used for testing, and the specific surface area is calculated by the BET (Brunauer Emmett Teller) method. The testing instrument can be the Tri-Star 3020 specific surface area pore size analysis tester of Micromeritics, USA.

[0085] In some embodiments, the specific surface area of ​​the graphite negative electrode active material can be 1.25 m 2 / g, 1.35m 2 / g, 1.45m 2 / g, 1.55m 2 / g, 1.65m 2 / g, 1.75m 2 / g, 1.85m 2 / g, 1.95m 2 / g or any range of values ​​between them.

[0086] The graphite negative electrode active material has a low specific surface area, so that the graphite negative electrode active material can not only take advantage of the relatively low mass content of crystalline carbon in the surface area to reduce battery expansion, but also reduce the probability of side reactions through the relatively low specific surface area to improve the cycle stability of the battery.

[0087] In some embodiments, the particle size distribution of the graphite negative electrode active material is (Dv90-Dv10) / Dv50 is 1.0-1.6, and can be 1.1-1.45.

[0088] In this article, the terms "Dv90" and "Dv10" refer to the particle sizes corresponding to when the cumulative volume distribution number of particles reaches 90% and 10% in the particle size distribution curve, respectively.

[0089] In the present application, the volume distribution particle size Dv90 and Dv10 of the graphite negative electrode active material can be tested by methods known in the art. As an example, referring to GB / T 19077-2016, a laser particle size analyzer is used for determination. The testing instrument can be a Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.

[0090] In some embodiments, the particle size distribution of the graphite negative electrode active material (Dv90-Dv10) / Dv50 is 1.0, 1.05, 1.1, 1.15, 1.2, 1.25, 1.3, 1.35, 1.4, 1.45, 1.5, 1.55, 1.6 or any range therebetween.

[0091] Controlling the particle size distribution of the graphite negative electrode active material within the above range is conducive to improving the compaction of the graphite negative electrode active material and improving the compaction density of the negative electrode film layer. In other words, the cold pressing pressure required for the negative electrode plate to achieve the same compaction density is smaller, thereby reducing the probability of cracking of the graphite negative electrode active material during the cold pressing process, and further improving the integrity of the graphite negative electrode active material during the processing process; and the small stress inside the graphite negative electrode active material particles is conducive to maintaining the long-period pore structure of the plate during the cycle process, and the original pore structure of the plate can be maintained during the cycle process, so that the lithium ion lithium insertion path remains unobstructed, while reducing the re-filming of the graphite negative electrode active material during the charging process, and improving the kinetic performance, cycle life and storage stability. Furthermore, the particle size distribution within the above range can also improve the uniformity of lithium insertion between the graphite negative electrode active material particles, reduce polarization, avoid lithium precipitation caused by uneven current density, and help achieve long-term cycle stability. In addition, the particle size distribution within the above range can also help improve the processing performance of the electrode, and will not affect the uniformity of slurry stirring due to excessive small particles in the graphite negative electrode active material, which is beneficial to improving the uniformity and stability of the electrode quality and helping to achieve long-cycle stability.

[0092] In some embodiments, the powder compaction density of the graphite negative electrode active material under a pressure of 49000N is 1.75g / cm 3 -1.88g / cm 3 , optional 1.78g / cm 3 -1.84g / cm 3 .

[0093] In this article, the term "powder compaction density" refers to the mass of powder particles per unit volume under a certain pressure.

[0094] In the present application, the powder compaction density of the graphite negative electrode active material under a pressure of 49000N can be tested by a method known in the art. As an example, referring to GB / T 24533-2009, 1g of graphite negative electrode active material powder is weighed and added to a bottom area of ​​1.327cm 2 The mold is pressurized to 5000 kg (equivalent to 49000 N), maintained for 30 seconds, then released and maintained for 10 seconds, and the powder compaction density of the graphite negative electrode active material under a pressure of 49000 N is measured by an electronic pressure testing machine (such as UTM7305 electronic pressure testing machine).

[0095] In some embodiments, the powder compaction density of the graphite negative electrode active material under a pressure of 49000N can be 1.75g / cm 3 , 1.78g / cm 3 , 1.82g / cm 3、1.84g / cm 3 , 1.85g / cm 3 、1.88g / cm 3 Or any range of values ​​in between.

[0096] Graphite negative electrode active materials with a powder compaction density within the above range are easy to maintain high particle integrity during the cold pressing process, which helps to improve the cycle life of the secondary battery.

[0097] In some embodiments, the tap density of the graphite negative electrode active material is 1.05 g / cm 3 -1.30g / cm 3 .

[0098] As used herein, the term "tapped density" refers to the mass per unit volume of powder in a container measured after being tapped under specified conditions.

[0099] In the present application, the tap density of the graphite negative electrode active material can be tested by a method known in the art. As an example, GB / T 5162-2006 can be referred to and a powder tap density tester can be used for determination. The test instrument can be Dandong Better BT-301, and the test parameters are as follows: vibration frequency 250±15 times / minute, amplitude 3±0.2mm, vibration number 5000 times, and measuring cylinder 25mL.

[0100] In some embodiments, the tap density of the graphite negative electrode active material is 1.05 g / cm 3 , 1.10g / cm 3 , 1.15g / cm 3 , 1.20g / cm 3 , 1.25g / cm 3 , 1.30g / cm 3 Or any range of values ​​in between.

[0101] In some embodiments, the gram capacity of the graphite negative electrode active material is 345 mAh / g-355 mAh / g, and can be optionally 347 mAh / g-353 mAh / g.

[0102] As used herein, the term "gram capacity" refers to the ratio of the amount of electricity that an active material can release to the mass of the active material.

[0103] In this application, the gram capacity of the graphite negative electrode active material can be tested by methods known in the art. As an example, the graphite negative electrode active material sample is fully stirred and mixed with the conductive agent carbon black and polyvinylidene fluoride (PVDF) in a proper amount of solvent NMP according to a mass ratio of 91.6:1.8:6.6 to form a uniform negative electrode slurry; the negative electrode slurry is evenly coated on the surface of the negative electrode current collector copper foil and dried and cold pressed; then the metal lithium sheet is used as the counter electrode, the polypropylene (PP) film is used as the isolation membrane, and the electrolyte is injected, wherein the electrolyte formula used is as follows: dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and ethylene carbonate (EC) are mixed according to a weight ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1.0 mol / L. Assembled into a CR2430 button cell in an argon-protected glove box. At 25°C, the button cell prepared above was first discharged at a constant current of 0.05C to 0.005V, then discharged at a constant current of 10μA to 0.005V, and left to stand for 5 minutes, and the first cycle discharge capacity of the button cell was recorded; then, the button cell was charged at a constant current of 0.1C to 2.0V, and the charging capacity of the button cell was recorded. The ratio of the charging capacity of the button cell to the mass of the graphite negative electrode active material sample is the gram capacity of the graphite negative electrode active material.

[0104] In some embodiments, the gram capacity of the graphite negative electrode active material is 345mAh / g, 346mAh / g, 347mAh / g, 348mAh / g, 349mAh / g, 350mAh / g, 351mAh / g, 352mAh / g, 353mAh / g, 354mAh / g, 355mAh / g, or any range therebetween.

[0105] The graphite negative electrode active materials with gram capacity within the above range will not undergo significant lattice expansion during the charge and discharge process due to the high graphitization of the graphite negative electrode active materials; nor will they be difficult to compact due to the low graphitization of the graphite negative electrode active materials. In order to achieve the same electrode compaction density, a higher cold pressing pressure is required, which will cause cracks during the cold pressing process and generate new interfaces during the cycle process to consume too much active lithium, thereby comprehensively improving the cycle life of the secondary battery.

[0106] In some embodiments, the graphite negative electrode active material is D / I G is 0.05-0.10, among which I D / I G is the ratio of the D peak intensity to the G peak intensity obtained from the Raman spectrum, I D Indicates that the Raman spectrum is at 1350±100cm -1 The D peak intensity at I GIndicates that the Raman spectrum is at 1580±100cm -1 The G peak intensity at .

[0107] In this application, the graphite negative electrode active material I D / I G Any known mode of Raman spectroscopy can be used for testing. As an example, referring to GB / T 40219-2021, an InVia Qontor (Reflex) Raman spectrometer is used for testing; a solid laser with a wavelength of 523nm is used as the light source, 100 points are sampled in an area of ​​100μm×100μm, and I D / I G The median is the median of the collected I arranged in order of size. D / I G The number in the middle of the data.

[0108] In some embodiments, the graphite negative electrode active material is D / I G It is 0.05, 0.06, 0.07, 0.08, 0.09, 0.10 or any numerical range therebetween.

[0109] Different from the active material coated with amorphous carbon on the surface of the graphite particle body, the graphite negative electrode active material provided in the embodiment of the present application has amorphous carbon on the surface and has a low surface disorder. The amorphous carbon in the active material coated with amorphous carbon on the surface of the graphite particle body is usually derived from the coated organic resin, which generates amorphous carbon under low-temperature carbonization, so that the amorphous carbon in the coating layer has a high surface disorder; while the surface area and the internal area of ​​the graphite negative electrode active material provided in the embodiment of the present application are derived from the same precursor and undergo the same heat treatment process, so the amorphous carbon of the graphite negative electrode active material is evenly distributed in the surface area of ​​the graphite negative electrode active material, so that the surface area of ​​the graphite negative electrode active material has a low crystalline carbon content and a low surface disorder. This allows the graphite negative electrode active material to take advantage of amorphous carbon, improve the battery's kinetic performance and reduce the cycle expansion rate of the electrode, while preventing excessive side reactions and a significant drop in battery capacity due to the high degree of disorder on the surface of the graphite negative electrode active material, thereby comprehensively improving the battery's cycle stability.

[0110] In some embodiments, the interlayer spacing of the surface region of the graphite negative electrode active material is recorded as d1, and the interlayer spacing of the internal region of the graphite negative electrode active material is recorded as d2, and the graphite negative electrode active material satisfies d1>d2; optionally, 0.3365nm≤d1≤0.3378nm; optionally, 0.3358nm≤d2≤0.3364nm.

[0111] As used herein, the term "interlayer spacing" refers to the shortest distance between two adjacent carbon atoms in the same carbon layer in graphite.

[0112] In the present application, the interlayer spacing of different regions of the graphite negative electrode active material can be tested using instruments and methods known in the art. For example, a high resolution transmission electron microscope (HRTEM) can be used for testing. The testing instrument can be a Spectra S / TEM scanning transmission electron microscope from Thermo Fisher Scientific.

[0113] In some embodiments, the interlayer spacing d1 of the surface region of the graphite negative electrode active material can be selected as 0.3365nm, 0.3367nm, 0.3369nm, 0.3371nm, 0.3372nm, 0.3373nm, 0.3375nm, 0.3378nm or any range therebetween. In some embodiments, the interlayer spacing d2 of the inner region of the graphite negative electrode active material can be selected as 0.3358nm, 0.3359nm, 0.3361nm, 0.3363nm, 0.3364nm or any range therebetween.

[0114] The interlayer spacing in the surface area is higher than that in the internal area of ​​the graphite negative electrode active material, which can play the role of a lithium insertion buffer layer, improve the wettability of the electrolyte to the graphite negative electrode active material, and improve the fast charging performance of the battery.

[0115] In some embodiments, the graphite negative electrode active material includes both primary particles and secondary particles; optionally, based on the total number of primary particles and secondary particles in the graphite negative electrode active material, the number of secondary particles accounts for less than or equal to 50%.

[0116] As used herein, the term "primary particles" refers to particles in a non-agglomerated state.

[0117] As used herein, the term "secondary particles" refers to particles in an agglomerated state formed by the aggregation of two or more primary particles.

[0118] Primary particles and secondary particles can be distinguished by observing the particle cross-section of the graphite negative electrode active material using a scanning electron microscope (SEM). In the present application, the proportion of the number of secondary particles in the graphite negative electrode active material can be tested by methods known in the art. As an example, a cross-section polisher (e.g., IB-09010CP argon ion cross-section polisher of JEOL, Japan) can be used to prepare the cross-section of the negative electrode sheet; then, referring to JY / T010-1996, a scanning electron microscope (e.g., Sigma 300 scanning electron microscope of ZEISS, Germany) is used to scan the cross-section of the negative electrode sheet, and multiple test areas are randomly selected in the test sample, and images of multiple test areas are obtained using a scanning electron microscope, and the number of graphite negative electrode active materials with secondary particle morphology in each image is counted. The ratio of the total number of graphite negative electrode active material particles, the average value of multiple statistical results is the number of secondary particles in the graphite negative electrode active material.

[0119] In some embodiments, based on the total number of primary particles and secondary particles in the graphite negative electrode active material, the number of secondary particles may be 50%, 40%, 30%, 20%, 10% or any range therebetween.

[0120] Graphite negative electrode active materials with a low proportion of secondary particles are conducive to maintaining the particle integrity of graphite negative electrode active materials during battery preparation, reducing the generation of new interfaces, reducing the consumption of active lithium during the cycle, and further improving the cycle stability of secondary batteries. At the same time, a certain number of secondary particles can reduce the expansion of the negative electrode while taking into account the kinetic performance of the secondary battery, so that the battery cell has a kinetic window for the entire life cycle, and will not cause lithium precipitation due to uneven current distribution, causing the battery capacity to decay sharply and the battery life to deteriorate sharply, thereby comprehensively improving the cycle stability of the battery.

[0121] The second aspect of the present application provides a method for preparing a graphite negative electrode active material, comprising the following steps: providing raw materials; processing the raw materials to obtain an intermediate product; graphitizing the intermediate product to obtain a graphitized product; screening the graphitized product to obtain a graphite negative electrode active material; the particle body of the graphite negative electrode active material includes an internal region and a surface region that at least partially surrounds the internal region, the surface region refers to a region extending 30 nm from the surface of the particle body of the graphite negative electrode active material to the interior of the particle, the mass percentage of crystalline carbon in the internal region is denoted as η1, the mass percentage of crystalline carbon in the surface region is denoted as η2, and 10%≤η1-η2≤35%.

[0122] Herein, the term "graphitization treatment" refers to the heat treatment process of carbon materials, which is the process in which the carbon materials transform from a two-dimensional carbon network structure to a three-dimensional ordered structure through "microcrystal" growth under high temperature.

[0123] In some embodiments, the maximum power of the graphitization process is 70%-90% of the rated power of the graphitization process equipment.

[0124] In some embodiments, the power of the graphitization process may be selected to be 70%, 75%, 80%, 85%, 90% of the rated power of the equipment, or any range of values ​​therebetween.

[0125] It can be understood that graphitization equipment refers to any device capable of graphitization, including but not limited to Acheson furnace, box furnace, inner series furnace, continuous graphitization, electric calcining furnace, medium frequency furnace, tubular furnace, etc. The rated power of graphitization equipment produced by different manufacturers may be different, and you can choose according to the actual situation.

[0126] The graphitization treatment power used in this application needs to be lower than the rated power of the graphitization treatment equipment to achieve uniformity of the temperature field during the graphitization treatment process, ensure the consistency of the material's gram capacity, and help improve the cycle life of the battery.

[0127] In some embodiments, the graphitization treatment equipment is an inner series furnace, and the rated power of the inner series furnace is 25000W-32000W.

[0128] In some embodiments, the graphitization treatment equipment is an Acheson furnace, and the rated power of the Acheson furnace is 28000W-30000W.

[0129] In some embodiments, the temperature of the graphitization treatment is 2600°C to 3000°C.

[0130] In some embodiments, the temperature of the graphitization treatment is 2600° C., 2700° C., 2800° C., 2900° C., 3000° C., or any range therebetween.

[0131] In some embodiments, the graphitization treatment time is 10 hours to 50 hours.

[0132] In some embodiments, the graphitization treatment time is 10 h, 15 h, 20 h, 25 h, 30 h, 35 h, 40 h, 45 h, 50 h, or any range therebetween.

[0133] In some embodiments, the graphitization treatment equipment is an internal series furnace, and the graphitization treatment time at maximum power is 10h-30h.

[0134] In some embodiments, the graphitization treatment equipment is an Acheson furnace, and the graphitization treatment is performed at maximum power for 30 hours to 50 hours.

[0135] In some embodiments, the raw material includes at least one of petroleum coke, needle coke, and asphalt coke, and needle coke may be selected.

[0136] As used herein, the term "petroleum coke" refers to coke formed by high-temperature carbonization of petroleum residue or petroleum asphalt.

[0137] As used herein, the term "needle coke" refers to coal tar pitch or petroleum pitch, which, after undergoing liquid phase carbonization to generate an anisotropic mesophase, can generate coke with a needle-like texture after undergoing processes such as high-temperature carbonization.

[0138] As used herein, the term "pitch coke" refers to a solid material produced by carbonizing coal tar pitch at high temperatures.

[0139] In some embodiments, the volume proportion of the fiber-type structure in the raw material is greater than or equal to 55%, and can be optionally 58%-70%.

[0140] In this article, "fibrous structure" is also called streamlined structure, which refers to the structure of the raw material with obvious fibrous texture observed under a microscope.

[0141] Usually, according to the morphological characteristics and isochromatic zone size of the coke material under a polarizing microscope, its microstructure can be divided into mosaic type, regional type and fiber type. Usually, the isochromatic zone microstructure with a size less than 30um is judged as mosaic type; the isochromatic zone microstructure with a size greater than 30um is judged as regional type, and the anisotropic strip-shaped isochromatic zone is judged as fiber type structure.

[0142] In this application, the volume proportion of the fiber structure in the raw material can be tested by methods known in the art. As an example, take the raw material according to GB 1997-89, mix the raw material crushed to 1mm, shrink it to 40g~50g, use a square hole sieve to take 0.07mm~1.0mm grade sample 4g~5g for film making; prepare powder coke and block coke light film according to MT 116.1-86, the diameter of the powder coke light film shall not be less than 22mm, and the volume occupied by the cement shall be less than 1 / 3; place the sample on a slide with glue, flatten it, and then place it on the stage to focus, calibrate the microscope and adjust the polarizer and analyzer to make them orthogonal. Insert the azurite inspection plate (1λ) to make the field of view present the interference color of primary red; determine the step length of the moving ruler to ensure that more than 400 effective measuring points are evenly distributed, and the point spacing is 0.3~0.5mm and the line spacing is generally 0.5~0.8mm. Starting from one end of the sample, determine the type of microstructure under the intersection of the crosshairs, and divide the number of effective measuring points of the fiber-type structure optical organization by the total number of statistical testing points as the volume content of the fiber-type structure in the raw material.

[0143] In some embodiments, based on the total volume of the raw material structure, the volume proportion of the raw material fiber structure can be selected to be 55%, 58%, 60%, 63%, 65%, 68%, 70% or any range therebetween.

[0144] Raw materials with more fiber-type structures are conducive to improving the compaction density and gram capacity of graphite negative electrode active materials, so that the graphite negative electrode active materials retain a high degree of integrity during the compaction process, and the battery has a high cycle life and good energy density; but too high a proportion of fiber-type structures will increase the cost and expansion rate of graphite negative electrode active materials and deteriorate kinetic performance. Raw materials with a volume proportion of fiber-type structures within the above range have both low costs and good gram capacity of graphite, and the battery cell has a full life cycle kinetic window, thereby comprehensively improving the long-term cycle life and electrochemical performance of the battery.

[0145] In some embodiments, the maximum gram capacity that can be achieved by the feedstock is greater than the gram capacity of the graphite negative electrode active material.

[0146] High-grade raw materials are used and the degree of graphitization is controlled so that the maximum gram capacity that the raw materials can achieve is not fully utilized, so that the mass percentage of crystalline carbon in the surface area of ​​the graphite negative electrode active material is lower than the mass percentage of crystalline carbon in the internal area of ​​the graphite negative electrode active material, so as to reduce the cyclic expansion of the graphite negative electrode active material and improve the cyclic stability of the graphite negative electrode active material.

[0147] In some embodiments, the processing of raw materials specifically includes: crushing, shaping and grading the raw materials to obtain a first precursor; granulating the first precursor to obtain a second precursor; and low-temperature carbonizing a mixture of the first precursor and the second precursor to obtain the intermediate product.

[0148] Crushing is the process of reducing the particle size of raw materials. The raw materials can be crushed by any mechanical device such as crusher, mechanical mill, etc.

[0149] Shaping and grading is the process of adjusting the particle size distribution of the raw material to obtain a first precursor that meets the particle size requirements. The particle size and particle size distribution of the first precursor can be regulated by adjusting the grading frequency and the air intake. In some embodiments, the grading frequency during the grading process is 40 Hz-50 Hz, and the air door opening is 20%-70%.

[0150] It can be understood that low-temperature carbonization of the first precursor and the second precursor to obtain the intermediate product includes low-temperature carbonization of a mixture of the first precursor and the second precursor to obtain the intermediate product; and also includes low-temperature carbonization of the first precursor and the second precursor to obtain the first intermediate product and the second intermediate product respectively. In some embodiments, the Dv50 particle size of the first precursor is 6.0 μm to 10.0 μm.

[0151] In some embodiments, the Dv50 particle size of the first precursor is 6.0 μm, 7.0 μm, 8.0 μm, 9.0 μm, 10.0 μm, or any range therebetween.

[0152] In some embodiments, the particle size distribution of the first precursor (Dv90-Dv10) / Dv50 is 1.05-1.75.

[0153] In some embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the first precursor is 1.05, 1.15, 1.25, 1.35, 1.45, 1.55, 1.65, 1.75 or any range therebetween.

[0154] In some embodiments, the tap density of the first precursor is 0.5 g / cm 3 ~0.7g / cm 3 .

[0155] In some embodiments, the tap density of the first precursor is 0.5 g / cm 3 , 0.55g / cm 3 , 0.6g / cm 3 , 0.65g / cm 3 , 0.7g / cm 3 Or any range of values ​​in between.

[0156] In some embodiments, the Dv50 particle size of the second precursor is 11.0 μm to 15.0 μm.

[0157] In some embodiments, the Dv50 particle size of the second precursor is 11.0 μm, 12.0 μm, 13.0 μm, 14.0 μm, 15.0 μm, or any range therebetween.

[0158] The second precursor is obtained by granulating the first precursor, and therefore, the second precursor mainly forms secondary particles in the graphite negative electrode active material.

[0159] Controlling the particle sizes of the first precursor and the second precursor helps to regulate the particle size and particle size distribution of the graphite negative electrode active material and improve the cycle stability of the battery.

[0160] In some embodiments, the temperature of low-temperature carbonization is 900° C.-1300° C., and the time of low-temperature carbonization is 24 h-240 h.

[0161] In some embodiments, the temperature of the low temperature carbonization may be selected to be 900° C., 1000° C., 1100° C., 1200° C., 1300° C., or any range therebetween.

[0162] In some embodiments, the low-temperature carbonization time may be 24 h, 50 h, 75 h, 100 h, 150 h, 200 h, 240 h, or any range therebetween.

[0163] [Negative electrode]

[0164] In some embodiments, the negative electrode plate includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector. For example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0165] In some embodiments, the negative electrode film layer includes the graphite negative electrode active material of the first aspect of the embodiment of the present application or the graphite negative electrode active material prepared by the method of the second aspect of the embodiment of the present application, thereby enabling the secondary battery to have high first coulombic efficiency, high energy density and good cycle performance.

[0166] In some embodiments, the compaction density of the negative electrode film layer is 1.5 g / cm 3 ~1.65g / cm 3 .

[0167] In the present application, the compaction density of the negative electrode film layer can be tested by methods known in the art. As an example, an electronic balance is used to weigh a negative electrode plate test sample with an area of ​​S, and the weight is recorded as W1, and a micrometer is used to measure the thickness T1 of the negative electrode plate. Then wipe off the weighed electrode film layer, weigh the weight of the negative electrode current collector, record it as W2, and use a micrometer to measure the thickness T2 of the negative electrode current collector. Then the compaction density of the negative electrode film layer PD = (W1-W2) / [(T1-T2)×S].

[0168] In some embodiments, the compaction density of the negative electrode film layer is 1.5 g / cm 3 , 1.55g / cm 3 , 1.6g / cm 3 , 1.65g / cm 3 Or any range of values ​​in between.

[0169] In some embodiments, the negative electrode film layer may further include other negative electrode active materials in addition to the above-mentioned graphite negative electrode active material. In some embodiments, the other negative electrode active materials include but are not limited to one or more of conventional natural graphite, other artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials and lithium titanate. The silicon-based material may include one or more of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite and silicon alloy material. The tin-based material may include one or more of elemental tin, tin oxide and tin alloy material.

[0170] In some embodiments, the negative electrode film layer may further include a negative electrode conductive agent. The present application has no particular restrictions on the type of the negative electrode conductive agent. As an example, the negative electrode conductive agent may include one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0171] In some embodiments, the negative electrode film layer may further include a negative electrode binder. The present application has no particular restrictions on the type of the negative electrode binder. As an example, the negative electrode binder may include one or more of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS).

[0172] In some embodiments, the negative electrode film layer may further include other additives. As an example, the other additives may include a thickener, such as sodium carboxymethyl cellulose (CMC), a PTC thermistor material, and the like.

[0173] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).

[0174] The negative electrode film layer is usually formed by coating the negative electrode slurry on the negative electrode current collector, drying and cold pressing. The negative electrode slurry is usually formed by dispersing the negative electrode active material, optional conductive agent, optional binder, and other optional auxiliary agents in a solvent and stirring them uniformly. The solvent can be N-methylpyrrolidone (NMP) or deionized water, but is not limited thereto.

[0175] The negative electrode plate does not exclude other additional functional layers in addition to the negative electrode film layer. For example, in some embodiments, the negative electrode plate described in the present application also includes a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode collector and the negative electrode film layer and disposed on the surface of the negative electrode collector; in some embodiments, the negative electrode plate described in the present application also includes a protective layer covering the surface of the negative electrode film layer.

[0176] [Positive electrode]

[0177] In some embodiments, the positive electrode plate includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector. For example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0178] The positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).

[0179] The positive electrode film layer generally includes a positive electrode active material, an optional binder, and an optional conductive agent. The positive electrode film layer is generally formed by coating a positive electrode slurry on the positive electrode current collector and then drying and cold pressing. The positive electrode slurry is generally formed by dispersing a positive electrode active material, an optional conductive agent, an optional binder, and any other components in a solvent and stirring evenly. The solvent can be N-methylpyrrolidone (NMP), but is not limited thereto. As an example, the binder for the positive electrode film layer may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin. As an example, the conductive agent for the positive electrode film layer includes one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0180] The positive electrode active material can be a positive electrode active material for secondary batteries well-known in the art.

[0181] When the secondary battery of the present application is a lithium-ion battery, the positive electrode active material may include, but is not limited to, one or more of lithium-containing transition metal oxides, lithium-containing phosphates, and their respective modified compounds. Examples of the lithium transition metal oxides may include, but are not limited to, one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their respective modified compounds. Examples of the lithium-containing phosphates may include, but are not limited to, lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium manganese iron phosphate, a composite material of lithium manganese iron phosphate and carbon, and their respective modified compounds.

[0182] In some embodiments, in order to further improve the energy density of the secondary battery, the positive electrode active material for the lithium-ion battery may include a lithium transition metal oxide having the general formula Li a Ni b Co c M d O e A f and its modified compounds, where 0.8 ≤ a ≤ 1.2, 0.5 ≤ b < 1, 0 < c < 1, 0 < d < 1, 1 ≤ e ≤ 2, 0 ≤ f ≤ 1, M is selected from one or more of Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, and B, and A is selected from one or more of N, F, S, and Cl.

[0183] In some embodiments, as an example, the positive electrode active material for the lithium-ion battery may include LiCoO2 、LiNiO 2 、LiMnO 2 、LiMn 2 O 4 、LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 (NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O 2 (NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O 2 (NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O 2 (NCM811), LiNi 0.85 Co 0.15 Al 0.05 O 2 、LiFePO 4 and LiMnPO 4 One or more of .

[0184] In the present application, the modified compound of each positive electrode active material mentioned above may be a compound obtained by doping and / or surface coating the positive electrode active material.

[0185] [Electrolytes]

[0186] In some embodiments, the electrolyte is an electrolyte solution, and the electrolyte solution includes an electrolyte salt and a solvent.

[0187] The type of the electrolyte salt is not particularly limited and can be selected according to actual needs.

[0188] When the secondary battery of the present application is a lithium ion battery, the electrolyte salt may include lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ), lithium perchlorate (LiClO 4 ) lithium hexafluoroarsenate (LiAsF 6 ), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO 2 F 2), one or more of lithium difluorobis(oxalate) phosphate (LiDFOP) and lithium tetrafluorooxalate phosphate (LiTFOP).

[0189] The type of the solvent is not specifically limited and can be selected according to actual needs. In some embodiments, as an example, the solvent may include ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS) and diethyl sulfone (ESE) One or more.

[0190] In some embodiments, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain properties of the secondary battery, such as additives that improve the overcharge performance of the secondary battery, additives that improve the high temperature performance of the secondary battery, and additives that improve the low temperature power performance of the secondary battery.

[0191] [Isolation film]

[0192] The present application has no particular limitation on the type of the isolation membrane, and any known porous structure isolation membrane with good chemical stability and mechanical stability can be selected.

[0193] In some embodiments, the material of the isolation membrane may include one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film. When the isolation membrane is a multi-layer composite film, the materials of each layer are the same or different.

[0194] In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet can be formed into an electrode assembly by a winding process or a lamination process.

[0195] Secondary battery

[0196] A fourth aspect of the embodiments of the present application provides a secondary battery.

[0197] The present application has no particular restrictions on the type of secondary battery. For example, the secondary battery can be a lithium-ion battery, etc. In general, a secondary battery includes a positive electrode plate, a negative electrode plate, and an electrolyte, etc. During the charge and discharge process of the secondary battery, active ions are embedded and removed back and forth between the positive electrode plate and the negative electrode plate, and the electrolyte plays a role in conducting active ions between the positive electrode plate and the negative electrode plate. The present application has no particular restrictions on the type of the electrolyte, which can be selected according to actual needs. For example, the electrolyte can be selected from at least one of a solid electrolyte and a liquid electrolyte (ie, an electrolyte). Secondary batteries using electrolytes and some secondary batteries using solid electrolytes may also include a separator, which is arranged between the positive electrode plate and the negative electrode plate to play an isolation role.

[0198] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0199] In some embodiments, the outer packaging can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT) and polybutylene succinate (PBS).

[0200] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 2 The secondary battery 5 is a square structure as an example.

[0201] In some embodiments, Figure 3 As shown, the outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation film can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, which can be adjusted according to demand.

[0202] The preparation method of the secondary battery of the present application is well known. In some embodiments, the positive electrode sheet, the separator, the negative electrode sheet and the electrolyte can be assembled to form a secondary battery. As an example, the positive electrode sheet, the separator and the negative electrode sheet can be formed into an electrode assembly through a winding process or a lamination process, and the electrode assembly is placed in an outer package, and the electrolyte is injected after drying, and the secondary battery is obtained through vacuum packaging, standing, forming, shaping and other processes.

[0203] In some embodiments of the present application, the secondary batteries according to the present application can be assembled into a battery module. The battery module can contain multiple secondary batteries, and the specific number can be adjusted according to the application and capacity of the battery module.

[0204] Figure 4 FIG. 4 is a schematic diagram of a battery module 4 as an example. Figure 4 As shown, in the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.

[0205] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0206] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0207] Figure 5 and Figure 6 FIG. 1 is a schematic diagram of a battery pack 1 as an example. Figure 5 and Figure 6 As shown, the battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3, wherein the upper box body 2 is used to cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.

[0208] Electrical devices

[0209] The present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack of the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device can be, but is not limited to, a mobile device (such as a mobile phone, a tablet computer, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.

[0210] The electrical device may select a secondary battery, a battery module or a battery pack according to its usage requirements.

[0211] Figure 7Schematic diagram of an electric device as an example. The electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the requirements of the electric device for high power and high energy density, a battery pack or a battery module may be used.

[0212] As another example, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. The electric device is usually required to be light and thin, and a secondary battery may be used as a power source.

[0213] Example

[0214] The following examples describe the disclosure of the present application in more detail, and these examples are only for illustrative purposes, as it is obvious to those skilled in the art that various modifications and variations are made within the scope of the disclosure of the present application. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are based on mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.

[0215] Example 1

[0216] (1) Preparation of graphite negative electrode active materials

[0217] The needle coke with a fiber structure of 60.8% was crushed; the crushed material was shaped and finely powdered to obtain the first precursor. The Dv50 particle size of the first precursor was 9.1 μm, the particle size distribution (Dv90-Dv10) / Dv50 was 1.35, and the tap density of the first precursor was 0.67 g / cm 3 .

[0218] A portion of the first precursor is granulated and reformed in a reactor to obtain a second precursor with a particle size Dv50 of 14.4 um;

[0219] The ungranulated first precursor and the second precursor are respectively placed in a kiln for carbonization at a carbonization temperature of 1150° C. and a carbonization time of 24 h to obtain a first intermediate product and a second intermediate product respectively;

[0220] The first intermediate product and the second intermediate product are respectively placed in an inner series furnace for graphitization treatment at a temperature of 2800°C. The rated power of the inner series furnace is 28000W, and the maximum power of the graphitization treatment is 22400W, which is 80% of the rated power of the equipment. The maximum power is maintained for 25 hours, and primary particles and secondary particles are obtained respectively.

[0221] The primary particles and the secondary particles are mixed uniformly in a mass ratio of 1:1, and the mixture is sieved to remove the magnetism to obtain the graphite negative electrode active material.

[0222] The crystalline carbon mass percentage η1 in the inner region of the graphite negative electrode active material is 87%, the crystalline carbon mass percentage η2 in the surface region is 65%, η1-η2=22%, the graphitization degree is 92.97%, and the specific surface area is 1.49m 2 / g, the volume distribution particle size Dv50 is 10.5μm, and the powder compaction density under a pressure of 49000N is 1.78g / cm 3 , gram capacity is 350.2mAh / g, I D / I G The particle size distribution is (Dv90-Dv10) / Dv50, and the interlayer spacing d1 in the surface region is 0.3373 nm. The interlayer spacing d2 in the internal region is 0.3360 nm. The particle size distribution (Dv90-Dv10) / Dv50 is 1.36.

[0223] (2) Preparation of negative electrode sheet

[0224] The graphite negative electrode active material prepared above, the conductive agent Super P, the thickener sodium carboxymethyl cellulose CMC-Na, and the binder styrene butadiene rubber SBR were mixed at a dry material mass ratio of 96:1:1.2:1.8, and then deionized water was added as a solvent. The mixture was stirred under the action of a vacuum mixer until the system was uniform to obtain a negative electrode slurry. The negative electrode slurry was evenly coated on the negative electrode current collector copper foil, and the negative electrode sheet was obtained after drying, cold pressing, and slitting. The compacted density of the negative electrode film layer is 1.60g / cm 3 , the surface density is 9.48mg / cm 2 .

[0225] (3) Preparation of positive electrode sheet

[0226] The positive electrode active material lithium iron phosphate (LFP), the conductive agent Super P, and the binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 97:1:2, and the solvent N-methylpyrrolidone (NMP) is added. The system is stirred under the action of a vacuum mixer until it becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained after drying, cold pressing, and slitting. The compaction density of the positive electrode film layer is 2.50g / cm 3 , the surface density is 19.48mg / cm 2 .

[0227] (4) Preparation of electrolyte

[0228] In an argon atmosphere glove box with a water content of less than 10 ppm, diethyl carbonate (DEC), ethyl methyl carbonate (EMC), and ethylene carbonate (EC) were mixed in a weight ratio of 1:1:1 to obtain an organic solvent, and then LiPF 6Dissolve in the above organic solvent to prepare an electrolyte with a concentration of 1.0 mol / L, and then add vinylene carbonate (VC), the content of VC being 2% of the total mass of the electrolyte.

[0229] (5) Preparation of isolation membrane

[0230] Polypropylene film is used as the isolation film.

[0231] (6) Preparation of lithium-ion batteries

[0232] The positive electrode sheet, separator and negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain an electrode assembly; the electrode assembly is placed in an outer package, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.

[0233] Embodiment 2-8

[0234] The preparation method is basically the same as that of Example 1, except that the raw material structure or preparation process is adjusted, thereby adjusting the crystallinity of the inner region and / or surface region of the graphite negative electrode active material. The specific preparation parameters are shown in Table 1.

[0235] Table 1

[0236]

[0237] Comparative Example 1

[0238] The preparation method of Comparative Example 1 is basically the same as that of Example 1, except that the maximum power of the graphitization treatment is 28000W (rated power of the equipment) and the constant power time at the maximum power is 35h, and there is no disordered layer in the surface area of ​​the prepared graphite negative electrode active material body particles.

[0239] Comparative Example 2

[0240] The preparation method is basically the same as that of comparative example 1, except that the surface of the graphite negative electrode active material prepared in comparative example 1 is subjected to carbon coating treatment. Specifically, the material prepared in comparative example 1 is mixed with the coating agent (asphalt) at 100%:3%, and the mixed product is subjected to carbonization treatment at a carbonization temperature of 1100°C and constant temperature heat treatment for 2 hours. After the material is cooled to room temperature, it is screened and demagnetized to obtain the finished material.

[0241] Performance Testing

[0242] (1) Negative electrode cold pressure rebound rate test

[0243] The thickness of the negative electrode sheet after cold pressing is L0. After the cold pressed negative electrode sheet is placed in an environment of 25°C and 10% humidity for 24 hours, the thickness of the negative electrode sheet is tested to be L1. The cold pressing rebound rate V0 of the negative electrode sheet is calculated by the following formula: V0 = (L1-L0) / L0.

[0244] (2) Negative electrode cycle expansion rate test

[0245] The thickness of the negative electrode sheet after cold pressing in each embodiment and comparative example is recorded as L0. Take the secondary batteries prepared in each embodiment and comparative example, and carry out charge and discharge tests in an environment of 25°C, and discharge at a constant current to 2.5V at a discharge current of 1.0C (i.e., the current value of completely discharging the theoretical capacity within 1h). Then, charge at a constant current to 3.65V at a charging current of 1.0C, continue to charge at a constant voltage to a current of 0.05C, let the fully charged battery stand for 5 minutes, and then discharge at a constant current to 2.5V at a discharge current of 1.0C. The discharge capacity at this time is recorded as C0. Charge the secondary battery to 3.65V at 25°C, disassemble the secondary battery and test the thickness of the negative electrode sheet at this time, which is recorded as L2. The cyclic expansion rate of the negative electrode sheet is: (L2-L0) / L0×100%.

[0246] (3) Cyclic stability test

[0247] At 60°C, the batteries of the above embodiments and comparative examples were charged at a constant current of 1C to a voltage of 3.65V, then charged at a constant voltage of 3.65V to a current ≤ 0.05C, and then discharged at a constant current of 1C to a voltage of 2.5V. This was a charge and discharge process, and the discharge capacity C1 of the first cycle was recorded. The charge and discharge cycles were repeated until the battery capacity decayed to 80% of the initial capacity C1, and the test was stopped, and the number of cycle tests was recorded.

[0248] Test Results

[0249] As can be seen from Table 2, the graphite negative electrode active material in which the difference in the mass percentage of crystalline carbon between the inner region and the surface region is 10%-35% can achieve improved battery cycle performance.

[0250] Table 2

[0251]

[0252] It can be seen from Table 3 that when 80%≤η1<95%, the battery can have both good gram capacity and long cycle life.

[0253] Table 3

[0254]

[0255] It can be seen from Table 4 that when 60%≤η2≤70%, the battery has low cold pressure rebound rate, cycle expansion rate and excellent cycle life.

[0256] Table 4

[0257]

[0258] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A graphite negative electrode active material, characterized in that: The particle body of the graphite negative electrode active material includes an internal region and a surface region that at least partially surrounds the internal region, wherein the surface region refers to a region extending 30 nm from the surface of the particle body of the graphite negative electrode active material to the interior of the particle, the mass percentage of crystalline carbon in the internal region is denoted as η1, the mass percentage of crystalline carbon in the surface region is denoted as η2, and 10%≤η1-η2≤35%.

2. The graphite negative electrode active material according to claim 1, characterized in that: 75%≤η1≤99%, optionally 80%≤η1≤95%.

3. The graphite negative electrode active material according to claim 1 or 2, characterized in that: 55%≤η2≤75%, optionally 60%≤η2≤70%.

4. The graphite negative electrode active material according to any one of claims 1 to 3, characterized in that The graphitization degree of the graphite negative electrode active material is 88%-95%, and can be optionally 90%-95%.

5. The graphite negative electrode active material according to any one of claims 1 to 4, characterized in that The volume distribution particle size Dv50 of the graphite negative electrode active material is 7.5 μm-14.5 μm, and can be optionally 8.5 μm-12.5 μm.

6. The graphite negative electrode active material according to any one of claims 1 to 5, characterized in that The graphite negative electrode active material satisfies at least one of the following: (1) The specific surface area of ​​the graphite negative electrode active material is 1.25 m 2 / g-1.95m 2 / g, optional 1.35m 2 / g-1.75m 2 / g; (2) The particle size distribution (Dv90-Dv10) / Dv50 of the graphite negative electrode active material is 1.0-1.6, and can be optionally 1.1-1.5; (3) The powder compaction density of the graphite negative electrode active material under a pressure of 49000N is 1.75g / cm 3 -1.88g / cm 3 , optional 1.78g / cm 3 -1.84g / cm 3 ; (4) The tap density of the graphite negative electrode active material is 1.05 g / cm 3 -1.30g / cm 3 ; (5) The gram capacity of the graphite negative electrode active material is 345 mAh / g-355 mAh / g, and can be optionally 347 mAh / g-353 mAh / g; (6) I of the graphite negative electrode active material D / I G is 0.05-0.10, among which I D / I G is the ratio of the D peak intensity to the G peak intensity obtained from the Raman spectrum, I D Indicates that the Raman spectrum is at 1350±100cm -1 The D peak intensity at I G Indicates that the Raman spectrum is at 1580±100cm -1 The G peak intensity at (7) The interlayer spacing of the surface region of the graphite negative electrode active material is denoted as d1, and the interlayer spacing of the inner region of the graphite negative electrode active material is denoted as d2, and the graphite negative electrode active material satisfies d1>d2; optionally, 0.3365nm≤d1≤0.3378nm; optionally, 0.3358nm≤d2≤0.3364nm; (8) The graphite negative electrode active material includes both primary particles and secondary particles; optionally, based on the total number of primary particles and secondary particles in the graphite negative electrode active material, the number of the secondary particles accounts for less than or equal to 50%.

7. A method for preparing a graphite negative electrode active material, characterized in that: The following steps are involved: Provide raw materials; Processing the raw materials to obtain intermediate products; performing graphitization treatment on the intermediate product to obtain a graphitized product; Screening the graphitized product to obtain a graphite negative electrode active material; The particle body of the graphite negative electrode active material includes an internal region and a surface region that at least partially surrounds the internal region, wherein the surface region refers to a region extending 30 nm from the surface of the particle body of the graphite negative electrode active material to the interior of the particle, the mass percentage of crystalline carbon in the internal region is denoted as η1, the mass percentage of crystalline carbon in the surface region is denoted as η2, and 10%≤η1-η2≤35%.

8. The preparation method according to claim 7, characterized in that: The graphitization treatment satisfies at least one of the following conditions: (1) The maximum power of the graphitization treatment is 70%-90% of the rated power of the graphitization treatment equipment; (2) The temperature of the graphitization treatment is 2600° C. to 3000° C.; (3) The graphitization treatment time is 10 h to 50 h.

9. The preparation method according to claim 7 or 8, characterized in that: The raw material includes one or more of petroleum coke, needle coke, and asphalt coke, and needle coke can be selected.

10. The preparation method according to claim 9, characterized in that: Based on the total volume of the raw material, the volume proportion of the fiber-type structure in the raw material is greater than or equal to 55%, and can be optionally 58%-70%.

11. The preparation method according to any one of claims 7 to 10, characterized in that: The processing of raw materials specifically comprises the following steps: crushing, shaping and classifying the raw materials to obtain a first precursor; Granulating the precursor to obtain a second precursor; The first precursor and the second precursor are carbonized at low temperature to obtain the intermediate product.

12. A negative electrode plate, characterized in that: The negative electrode sheet comprises the graphite negative electrode active material according to any one of claims 1 to 6 or the graphite negative electrode active material prepared by the preparation method according to any one of claims 7 to 11.

13. The negative electrode sheet according to claim 12, characterized in that: The compaction density of the negative electrode film layer is 1.5 g / cm 3 ~1.65g / cm 3 .

14. A secondary battery, characterized in that: Including the negative electrode sheet as described in claim 12 or 13.

15. An electrical device, characterized in that: Includes the secondary battery as claimed in claim 14.

Citation Information

Patent Citations

  • Composite graphite material and preparation method thereof, negative pole piece and secondary battery

    CN115810724A

  • Multilayer negative electrode active material, method for preparing same, and lithium secondary battery comprising same

    CN116830304A

  • Graphite-based negative electrode active material and manufacturing method thereof

    JP2022165614A

  • Artificial graphite, secondary battery, method for the preparation thereof, and apparatus

    US20210399301A1

Cited By

  • Secondary battery, electric device, artificial graphite and preparation method thereof

    CN119852316A

  • Graphite particles, preparation method thereof, battery and energy storage device

    CN120657123A

  • Graphite material, preparation method of graphite material and battery

    CN121292426A